2001
DOI: 10.1007/s004240100005
|View full text |Cite
|
Sign up to set email alerts
|

The endurance training effect on the oxygenation status of an isometrically contracted forearm muscle

Abstract: The aim of the study was to find the influence of training on the oxygenation status of a forearm muscle during submaximal isometric contraction. Six subjects performed a test of isometric contraction of a forearm muscle by continuous pressing of a handgrip dynamometer with a force of 15 kp, until exhaustion. The continuous measurements of oxygen saturation (%) (OXY), concentration of oxygenated haemoglobin (pM) (OXYHb), deoxygenated haemoglobin (pM) (DEOXYHb) and total haemoglobin (pM) (TOTHb) in blood, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 4 publications
2
6
0
Order By: Relevance
“…The higher Deoxy[Hb + Mb]-increase in specifi cally trained subjects suggests that they show a higher increase in capillary O 2 -extraction, compared to untrained controls. This is in line with the results of Usaj [ 33 ] which showed that after 4 weeks of endurance training an increase in relative deoxygenated haemoglobin concentration and endurance time during sustained submaximal isometric handgrip exercise (at 30 % MVC) was visible. The author suggested that a certain number of capillaries may open as a result of isometric endurance training, increasing O 2 consumption capacity as a result of increased O 2 availability.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…The higher Deoxy[Hb + Mb]-increase in specifi cally trained subjects suggests that they show a higher increase in capillary O 2 -extraction, compared to untrained controls. This is in line with the results of Usaj [ 33 ] which showed that after 4 weeks of endurance training an increase in relative deoxygenated haemoglobin concentration and endurance time during sustained submaximal isometric handgrip exercise (at 30 % MVC) was visible. The author suggested that a certain number of capillaries may open as a result of isometric endurance training, increasing O 2 consumption capacity as a result of increased O 2 availability.…”
supporting
confidence: 92%
“…Isometric contraction is characterized by restricted local blood fl ow [ 10 , 27 , 34 ] , since the intramuscular pressure increases even at very low isometric contraction intensities [ 9 ] . Therefore, the delivery of oxygen and wash out of muscle metabolites may become limited, which aff ects the duration of such a contraction [ 33 ] . However, literature suggests that when fatiguing isometric contractions are performed at low levels ( ≤ 30 % ments from the M. Vastus Lateralis.…”
Section: Quadriceps Muscle Fatigue In Trained and Untrained Boysmentioning
confidence: 99%
“…To date, four studies have used NIRS to examine the effects of exercise training on muscle deoxygenation: Costes et al (2001); Usaj (2001); and Puente-Maestu et al (2003). These studies all showed that NIRS is a promising technique that could be used to examine the influence of exercise training on muscle oxygenation and reoxygenation following exercise (Table 2).…”
Section: Exercise Training Studiesmentioning
confidence: 99%
“…In the study by Usaj (2001), the use of NIRS in a group of 6 male subjects showed that a 4-week endurance-training program of the forearm musculature increased submaximal isometric contraction duration. Although maximal isometric force development with training was not significantly affected, the increased duration of submaximal contraction was likely related to changes in muscle characteristics with training, and this resulted in part in an observed greater deoxygenation before termination of muscular contraction.…”
Section: Exercise Training Studiesmentioning
confidence: 99%
“…Squeezing of a rubber ring at an intensity of about 30% of Maximal Voluntary Contraction (MVC) to fatigue, using single and multiple repetitions during a single training session and separated by suYcient recovery intervals, may increase the duration of isometric contractions of forearm muscles (Unaj 2001). A positive training eVect could occur mainly at intensities and durations corresponding to training intensity.…”
Section: Introductionmentioning
confidence: 99%